2012
DOI: 10.1016/j.juro.2011.10.138
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience and Results With a New Adjustable Transobturator Male System for the Treatment of Stress Urinary Incontinence

Abstract: The treatment of male stress urinary incontinence with the ATOMS is safe and effective. It is an excellent first or second line treatment for mild to moderate male stress urinary incontinence, even after external irradiation. The option of long-term, minimally invasive adjustment to respond to patient needs is a significant advantage of this new implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 22 publications
7
63
0
3
Order By: Relevance
“…Adjustable sling-like ATOMS is an excellent option in patients with mild-tomoderate incontinence or with new onset cognitive/manual impairment or not willing to undergo AUS reimplantation [28]. In the original clinical description of Seweryn et al [11], ATOMS system was presented as an excellent first-or second-line treatment for mild-to-moderate male SUI, even after external irradiation. Later a singlecenter experience confirmed that ATOMS represents an efficient alternative even for severe incontinence [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adjustable sling-like ATOMS is an excellent option in patients with mild-tomoderate incontinence or with new onset cognitive/manual impairment or not willing to undergo AUS reimplantation [28]. In the original clinical description of Seweryn et al [11], ATOMS system was presented as an excellent first-or second-line treatment for mild-to-moderate male SUI, even after external irradiation. Later a singlecenter experience confirmed that ATOMS represents an efficient alternative even for severe incontinence [29].…”
Section: Discussionmentioning
confidence: 99%
“…One study with the first-generation inguinal titanium port device described a high complication and explantation rate, but patient satisfaction was very high and 56% of the patients in this cohort would recommend the system to their best friends [32]. Within ATOMS literature, uretral erosion has been reported only twice, in a case associated to perineal infection [32] and in another patient who had undergone surgery for incontinence on 4 separate occasions and had experienced erosion of an AUS 6-month before receiving the ATOMS implant [11]. No more cases were reported in large multicenter studies [14,30] or in any other series so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adjustable devices offer a great advantage over the non-adjustable ones: their ability to be adapted to changes in patients' conditions. Examples of adaptable devices are the Argus (Promedon, Argentina), Remeex (Neomedic, Spain), ATOMS (A.M.I., Austria) and ProACT™ (Uromedica, USA) devices (5,(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%